The USAID and the teaching of mathematics in Rio Grande do Norte A USAID e o Ensino de Matemática no Rio Grande do Norte - Arlete de Jesus Brito (Universidade Estadual Paulista, 2008)
In the 1960s occurred great changes in the general education and, specially in the mathematical teaching, throughout Brazil. Besides the Law "Diretrizes e Bases" for Education (law 4024/1961), such changes also was occurred by opposite educational movements. In one side, those ones that valorized the popular education and culture and, for the other side, the international agreements between universities and government organs, like SUDENE and MEC, with United States Agency for International Development (USAID). These agreements purposed the cultural alignment. In this article we will expose some of these agreements and their interference in two courses for teachers´ education. These teachers taught mathematics for the elementary school, in Rio Grande do Norte. Keywords: Teacher Education. USAID. Modern Mathematics Movement. A década de 1960 foi marcada por grandes mudanças na educação em geral e, especificamente no ensino de matemática, em todo o Brasil. Além da Lei de Diretrizes e Bases para a Educação (lei 4024/1961) tais mudanças, elas se materializaram também por meio de movimentos que possuíam tanto objetivos opostos, quanto modos de efetivação díspares. Por um lado, podemos considerar os movimentos de valorização da educação e da cultura popular e por outro, têm-se os acordos internacionais entre universidades e órgãos governamentais, como a SUDENE e o MEC com a United States Agency for International Development (USAID) que visavam ao alinhamento cultural. Neste artigo exporemos alguns destes acordos e sua interferência em dois momentos da formação de professores da escola primária, na área de ensino de matemática, no Rio Grande do Norte. Palavras-chave: Formação de Professores. USAID. Movimento da Matemática Moderna.